Virological Examination of Bovine Mammary Lymph Nodes - Woods, G. T. (1970)
Mammary lymph nodes from 42 Hereford cows culled for poor reproductive performance were examined for cytopathogenic virus and hemadsorption. No evidence of viral infection was detected using the methods employed. Serum from all the animals gave positive reactions to the hemagglutination-inhibition test for bovine myxovirus parainfluenza 3. Six of 12 had neutralizing antibody against bovine virus diarrhea virus, but none of the 12 had neutralizing antibodies against infectious bovine rhinotracheitis virus.